Implementasi Nilai Toleransi Antarberagama di Sekolah: Sikap Guru Katolik Terhadap Tradisi Lebaran Prespektif Pendidikan Islam - Nita Jannatun Ni’mah; Agus Khunifi; Fihris Fihris (LPPM Institut Pendidikan Nusantara Global, 2026)
This article examine tions of their Muslim colleagues in elementary schools as a reflection of the values of Islamic Religious Education (PAI) in building a harmonious and inclusive educational environment. This qualitative research, using a case study approach, used interviews with a Catholic teacher to understand forms of tolerant attitudes such as greeting Eid al-Fitr greetings, participating in halal bihalal (gatherings), and involvement in interfaith activities. The results indicate that Islamic Religious Education (PAI) values, such as brotherhood, compassion, mutual respect, and peace, are reflected in the behavior of teachers who serve as role models for students. Factors supporting tolerant attitudes include teacher role models, understanding of tolerance values, and emotional maturity and empathy. This research confirms that education plays a crucial role in enhancing humanitarian values and tolerance amidst diversity, supporting the creation of a harmonious society in accordance with the spirit of Indonesian diversity.